(untitled) - Lugt, Herbert Vander (U.S.A, 1983)
There's a New Day Coming... the day of Christ's return. Believers are looking forward to it with bright hope and deep longing. What will that day be like? Do we know when it will arrive? And what will be the order of the endtime events prophesied in the Bible? This book has been written to answer these questions. Among its chapters you will find detailed discussions of the major coming events.
Keywords: Eschatology